Factors Predicting Environment-Friendly Consumer Behavior: Reducing Plastic Consumption in Oman - Salmi, Hilal Al; Ali, Asan; Ahmed, Fauziah Sh. (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2022)
Environment-friendly behavior is the need of the hour. The United Nation’s Sustainable Development Goals (SDGs) have placed a collective burden on countries around the globe to undertake measures to safeguard the planet by starting with their own territories and water bodies. The Sultanate of Oman is an example of a country where there is top-down participation in environmental initiatives. Nevertheless, it appears that the initiatives have to be current and on-going, accompanied by stringent monitoring and evaluation. In this context, the present study undertakes a scoping review of literature related to the factors that influence environment-friendly behavior in different individual and social contexts. The use of the Theory of Planned Behavior (TPB), a popular theoretical framework in recent studies on environment-friendly behavior, to identify the factors of environment-friendly behavior was utilized as the basis for the review. A set of 50 empirical studies from 2012-till February 2022 were included in the scoping review. Academic and managerial implications are offered based on the findings. Overall, it could be seen that despite considerable research in the area, environmental awareness was a significant contributor to environment-friendly behavior and the study recommends governmental, public and private attention to increasing environment-friendly behavior among citizens. Research paper Keywords: Theory of Planned Behavior, Oman, Consumer Behavior, Environment-Friendly Behavior Factors Reference to this paper should be made as follows: Al Salmi, H., Ali, A., & Ahmad, F. S. (2022). Factors Predicting Environment-Friendly Consumer Behavior: Reducing Plastic Consumption in Oman. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 170–215.